Gadolinium-Conjugated Gold Nanoshells for Multimodal Diagnostic Imaging and Photothermal Cancer Therapy - Coughlin, Andrew J. (2013)
Multimodal imaging offers the potential to improve diagnosis and enhance the specificity of photothermal cancer therapy. Toward this goal, we have engineered gadolinium-conjugated gold nanoshells and demonstrated that they enhance contrast for magnetic resonance imaging, X-Ray, optical coherence tomography, reflectance confocal microscopy, and two-photon luminescence. Additionally, these particles effectively convert near-infrared light to heat, which can be used to ablate cancer cells. Ultimately, these studies demonstrate the potential of gadolinium-nanoshells for image-guided photothermal ablation.